Quid Pro Quo: Technology Capital Transfers for Market Access in China - Holmes, Thomas J.; McGrattan, Ellen R.; Prescott, Edward C. (Review of Economic Studies, 2015)
By the 1970s, quid pro quo policy, which requires multinational firms to transfer technology in return for market access, had become a common practice in many developing countries. While many countries have subsequently liberalized quid pro quo requirements, China continues to follow the policy. In this article, we incorporate quid pro quo policy into a multicountry dynamic general equilibrium model, using microevidence from Chinese patents to motivate key assumptions about the terms of the technology transfer deals and macroevidence on China's inward foreign direct investment (FDI) to estimate key model parameters. We then use the model to quantify the impact of China's quid pro quo policy and show that it has had a significant impact on global innovation and welfare.